Hemorrhage‐Induced Interleukin‐1 Receptor Pathway in Lung Is Suppressed by 3, 5‐Bis(2‐Fluorobenzylidene)‐4‐Piperidone in a Rat Model of Hypovolemic Shock. Issue 8 (22nd April 2014) - Yadav, Vivek R.; Vilekar, Prachi; Awasthi, Shanjana; Awasthi, Vibhudutta
Abstract Severe blood loss in victims of trauma creates an exaggerated inflammatory background that contributes to the development of intravascular coagulopathy and multiple organ dysfunction syndrome. We hypothesized that treatment with diphenyldifluoroketone EF24, an inhibitor of nuclear factor kappa‐B, would have salutary effects in hemorrhagic shock. The objective of this study was to investigate the effect of EF24 on the expression of the interleukin‐1 receptor (IL‐1R) superfamily in a rat model of hypovolemic shock. Hypovolemia was induced by gradually withdrawing approximately 50% of circulating blood, and EF24 was administered intraperitoneally (0.2 mg/kg) in 50 μL of saline. After 6 h of shock, lung tissue was probed immunohistochemically and by immunoblotting to study the expression of Toll‐like receptor 4 (TLR4), IL‐1R, suppression of tumorigenicity 2 (ST2), and single immunoglobulin IL‐1R‐related (SIGIRR). The tissue‐associated pro‐inflammatory cytokines, tumor necrosis factor alpha (TNF‐α) and IL‐6, were measured by enzyme‐linked immunosorbent assay. We observed a reduction in immunoreactive TLR4 and IL‐1R1 in lung tissue of rats treated with EF24. Simultaneously, the pulmonary expression of ST2 and SIGIRR (the putative down‐regulators of the pro‐inflammatory IL‐1R pathway) was increased in EF24‐treated hemorrhaged rats. The concentration of hemorrhage‐induced TNF‐α and IL‐6 in lung tissue homogenates was also reduced by EF24 treatment. These results confirm our previous in vitro observations in lipopolysaccharide‐stimulated dendritic cells that EF24 beneficially modulates the IL‐1R pathway and suggest that it could be investigated as an adjunct therapeutic in managing inflammation associated with hemorrhagic shock.